2004
DOI: 10.1590/s0074-02762004000700013
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Mycobacterium kansasii isolates in the State of São Paulo between 1995-1998

Abstract: Mycobacterium kansasii is the most common cause of pulmonary nontuberculous mycobacteria infection and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…Molecular typing methods demonstrated that M. kansasii is a heterogeneous species with several distinct subtypes (Ross et al, 1992;Alcaide et al, 1997;Iinuma et al, 1997;Picardeau et al, 1997;Richter et al, 1999;Gaafar et al, 2003;Taillard et al, 2003). PCR and restriction enzyme analysis (PRA) of the hsp-65 gene has been widely applied to studies concerning M. kansasii genotypic characterization (Ross et al, 1992;Picardeau et al, 1997;Richter et al, 1999;Taillard et al, 2003;Chimara et al, 2004). To date, such investigations have suggested that M. kansasii of PRA type I is the most prevalent type from clinical isolates worldwide and is only rarely isolated from the environment (Tortoli, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular typing methods demonstrated that M. kansasii is a heterogeneous species with several distinct subtypes (Ross et al, 1992;Alcaide et al, 1997;Iinuma et al, 1997;Picardeau et al, 1997;Richter et al, 1999;Gaafar et al, 2003;Taillard et al, 2003). PCR and restriction enzyme analysis (PRA) of the hsp-65 gene has been widely applied to studies concerning M. kansasii genotypic characterization (Ross et al, 1992;Picardeau et al, 1997;Richter et al, 1999;Taillard et al, 2003;Chimara et al, 2004). To date, such investigations have suggested that M. kansasii of PRA type I is the most prevalent type from clinical isolates worldwide and is only rarely isolated from the environment (Tortoli, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…M. kansasii was the second most frequent (3.2%), the first being the M. avium complex. (10) The concept that NTM can colonize the lungs without triggering a disease is controversial, especially when the agent is the M. kansasii, M. gordonae or M. avium complex. In order to classify such colonization as a disease according to the criteria established by the American Thoracic Society,(3) there must be pulmonary lesions and NTM identified in multiple cultures of at least three sputum samples, or the histological analysis should demonstrate a granulomatous chronic process and positive tissue culture.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, PCR-restriction analysis (PRA) of part of the gene encoding the 65-kDa heat shock protein (hsp65) 15 has been widely used for diagnostic purposes. 9,10,[16][17][18] This method is based on the amplification of a 441-bp fragment of the hsp65 gene present in all mycobacteria, followed by digestion of the PCR product with the restriction enzymes BstEII and HaeIII. By combining both restriction patterns a species assignment is possible based on comparison with patterns described in published algorithms 15,16 or available from an Internet database (http://app.chuv.ch/prasite).…”
Section: Introductionmentioning
confidence: 99%